Anthropological and psychoanalytical observation: theoretical and methodological dialogues in a doctorate programme in mother and child health Observação antropológica e psicanalítica: diálogos teórico-metodológicos num programa de doutorado em saúde materno infantil - Marisa Amorim Sampaio; Ana Rodrigues Falbo; Katia Virginia de O. Feliciano; Maria do Carmo Camarotti; Michael Rustin; Lisa Miller (Instituto Materno Infantil de Pernambuco, 2012)
Participant observation can vary considerably depending on the theoretical inspiration, nature/design of the research and relationship researcher-subjects. In the ethnographic study developed in Brazil (July 2009 - August 2010), among other techniques used, Bick's observation (rooted in psychoanalysis) was introduced and adapted. The aim was to understand processes involved in the communication between professionals at a Family Health Strategy and mothers/dyads (mother-baby) about breast feeding. Based on this study, a sandwich project was designed: to develop a deeper understanding of Bick's theoretical and practical approach, its relevance for research and broader applications; to promote a transdisciplinary dialogue between anthropological and psychoanalytic observation. As a student at Tavistock (UK) I attended seminars and developed observations in another variation of the setting. Aware of the ethics of the method, Tavistock has been widening its' scope, not seeing it as a unique model, but a comprehensive way of thinking human uniqueness, facilitating the researcher's capacity for self-analysis and a diversity of applications. Although my reflections are preliminary, the potential of Bick's to innovate research methods cannot be ignored. In the contemporary field of mother-child health we do not face a single concept of science, but new/renewed paradigms of thought and diversity of methods. A observação participante pode variar consideravelmente dependendo da inspiração teórica, natureza/desenho do estudo e da relação pesquisador-sujeitos. Num estudo etnográfico desenvolvido no Brasil (Julho 2009 - Agosto 2010), dentre outras técnicas utilizadas, a observação Bick (ancorada na psicanálise) foi introduzida e adaptada. O objetivo foi compreender os processos envolvidos na comunicação profissionais da Estratégia de Saúde da Família e mãe/díades (mãe-bebê) sobre amamentação. Com base neste, um projeto sanduíche foi concebido visando: desenvolver compreensão aprofundada da abordagem teórico-prática do método Bick, sua relevância para a pesquisa e aplicações abrangentes; promover diálogo transdisciplinar entre observação antropológica e psicanalítica. Como estudante na Tavistock (Reino Unido) participei de seminários e desenvolvi observações noutra variação do setting Bick. Ciente da ética do método, a Tavistock tem abrangido seu escopo, não tomando o Bick como um modelo único a ser seguido, mas um modo abrangente de abordar a singularidade humana, promovendo a capacidade auto-analítica do pesquisador e uma diversidade de aplicações. Apesar das reflexões ainda serem preliminares, o potencial do Bick para inovar métodos de pesquisa não pode ser ignorado. No campo atual da saúde materno infantil não lidamos com um conceito único de ciência, porém paradigmas de pensamento novos/renovados e uma diversidade de métodos.